Strain Analysis in the Detection of Myocardial Infarction at the Acute and Chronic Stages. Issue 3 (28th September 2015) - Bachner‐Hinenzon, Noa; Malka, Assaf; Barac, Yaron; Meerkin, David; Ertracht, Offir; Carasso, Shemy; Shofti, Rona; Leitman, Marina; Vered, Zvi; Adam, Dan; Binah, Ofer
Abstract : Background: Myocardial ischemia causes contractile dysfunction in ischemic, stunned, and tethered regions with larger infarcted zones having a negative prognostic impact on patients' outcomes. To distinguish the infarcted myocardium from the other regions, we investigated the diagnostic potential of circumferential strain (CS) and radial strain (RS) during the acute and chronic stages of myocardial infarction. Methods: Ten pigs underwent 90‐minute occlusion of the left anterior descending artery, followed by reperfusion. Echocardiography was performed at baseline, after 90‐minute occlusion, and at 2 hours, 30, and 60 days postreperfusion. CS and RS were measured using speckle tracking echocardiography. Subsequently, the pigs were sacrificed, and histological analysis for infarct size was performed. Results: After 90‐minute occlusion, reduced strains were detected for all segments (infarcted anterior wall – baseline: CS: −17.6 ± 5.7%, RS: 54.4 ± 16.9%; 90 min: CS: −10.3 ± 3.0%, RS: 23.3 ± 7.0%; tethered posterior wall – baseline: CS: −18.4 ± 3.5%, RS: 68.7 ± 21.1%; 90 min: CS: −10.7 ± 6.4%, RS: 34.5 ± 14.7%, P < 0.001). However, postsystolic shortening was detected only in the infarcted segments, and the time‐to‐peak CS was 25% longer (P < 0.05). At 30 and 60 days postreperfusion, time‐to‐peak CS could only detect large scars in the anterior and anterior‐septum walls (P < 0.05), while peak CS also detected smaller scars in the lateral wall (P < 0.05). RS failed to distinguish between normal, stunned/tethered, and infarcted myocardium. Conclusions: During occlusion and 2 hours postreperfusion, time‐to‐peak CS could distinguish between infarcted and stunned/tethered myocardial segments, while at 30 and 60 days postreperfusion, peak CS was the best detector of infarction.